Assessment of drum seeding technology of rice cultivation through on farm trials and front-line demonstration: Evaluation of rice drum seeding in Pedapalli - Yasa, Venkanna; Pilli, Kiran; Bheemisetti , Bhaskar Rao; Amanaganti, Srinivas; Thatikonda , Vinod Kumar; Baireneni, Navya; Archana, K; Bandari, Naresh; T, Suresh Kumar (ORYZA-An International Journal of Rice, 2026)
In the majority of countries, rice is the staple crop and the cultivation is a labour-intensive and expensive process. Farmers are experiencing difficulty in the adoption of transplanting due to the shortage of labour and high labour wages and the delay in release of water from canals or the low availability of water during early kharif. In order to overcome the problems, farmers are looking for new and simple technologies. Krishi Vigyan Kendra (KVK) scientists also searched for the simplest and most effective technology based on initial feedback from the farmers. We finally determined that drum seeding technique is quite simple, requires awareness and training to adopt the technology. To evaluate the technology, KVK, Ramagirikhilla, has introduced the drum seeding technology in Peddapalli district of Telangana in the year 2012-13 and continued its assessment through On Farm Trials (OFT) and Front Line Demonstration (FLD) for seven years from 2012-13 to 2018-19 covering an area of 23.20 ha in 16 locations. The results revealed that there was an increase of 14.74 % yield (58.97 q ha-1) compared to farmer's practice (51.57 q ha-1). Overall data on seven years' assessment showed an extension gap of 7.4 q ha-1, a technology gap of 16.03 q ha-1, and a technology index of 21.37%. Drum seeding technology resulted in better net returns and an increase of Rs. 11,895.71 ha-1 over farmers' practice and achieved higher benefit cost ratio (2.88) than farmers' practices (2.32). The adoption of drum seeding technology increased from negligible to 343.30% with an overall adoption level of 182.41% and a horizontal spread from 0 ha to 1387 ha during the study period.